Considerações sobre a vegetação na Reserva Ecológica do Panga (Uberlândia) - Schiavini, Ivan; Araújo, Glein Monteiro (Sociedade & Natureza, 1989)
Considerações sobre a vegetação na Reserva Ecológica do Panga (Uberlândia)